An insight of accountability practices in non-governmental organizations (NGOs): the case of Yemen - Abdullah Ahmeed, Abdulwahed Hamoud; Zainol, Zaini; Mokhtar, Norsyahida (SSBFNET- Center for Strategic Studies in Business & Finance, 2022)
The increase of scandals involving non-governmental organizations (NGOs) has provoked concerns from the public for their accountability. In the case of Yemen, the NGOs receive financial supports from both local and international donors. These organisations, however, are not obliged to disclose how they manage the donation funds, although the donors usually outline specific requirements on how the funds should be utilised. At the same time, the success of projects undertaken by the NGOs funded by the donors can help to enhance the organisation’s reputation and legitimize its activities to secure more funds. This study investigated the level of accountability practices in the Yemeni local NGOs. A questionnaire survey was sent to 75 active local NGOs. The findings show that the level of accountability practices among local NGOs is moderate. Most of these organisations evaluated the impact of their projects at their completion. However, they tend to avoid an independent assessment of any third-party. They also restricted the local communities’ involvement in determining where and how the money of the project should be spent. This suggests that the local NGOs are more likely to be “seen” as being accountable rather than being accountable. A further improvement perhaps through policy making is thus necessary to ensure effective accountability practices in funds management of the NGOs.